2017
DOI: 10.3390/toxics6010002
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Impact of the Herbicide Roundup on Human Sperm Motility and Sperm Mitochondria

Abstract: Toxicants, such as herbicides, have been hypothesized to affect sperm parameters. The most common method of exposure to herbicides is through spraying or diet. The aim of the present study was to investigate the effect of direct exposure of sperm to 1 mg/L of the herbicide Roundup on sperm motility and mitochondrial integrity. Sperm samples from 66 healthy men who were seeking semen analysis were investigated after written informed consent was taken. Semen analysis was performed according to the World Health O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…Thirty (30) healthy men volunteered for semen analysis for the study during 2016 and gave written informed consent; Institutional Review Board approval of the study was also obtained (protocol number: 2538/15.6.2016). The present study is following previous work concerning the effect of Roundup on human sperm motility and sperm mitochondria [ 14 ]. All of the subjects were living in the agricultural region of Greece, Thessaly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty (30) healthy men volunteered for semen analysis for the study during 2016 and gave written informed consent; Institutional Review Board approval of the study was also obtained (protocol number: 2538/15.6.2016). The present study is following previous work concerning the effect of Roundup on human sperm motility and sperm mitochondria [ 14 ]. All of the subjects were living in the agricultural region of Greece, Thessaly.…”
Section: Methodsmentioning
confidence: 99%
“…Portions of 0.5 mL of the total volume of each specimen were centrifuged at 2000 rpm for 5 min and the supernatant from each sample was carefully discarded, while the pellet was resuspended in 1 mL of pre-warmed buffer solution (Gamete Buffer, William Cook Australia PTY LTD ® , Brisbane, Australia) containing glyphosate at a final concentration of 0.36 mg/L. The rationale for the dose of 0.36 mg/L glyphosate was that in the previous work [ 14 ] we used 1 mg/L Roundup at final concentration which corresponded to 0.36 mg/L glyphosate. Therefore, the obtained results from glyphosate will be at least explanatory when compared to the results obtained by Roundup.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and epidemiological studies published in recent decades point to a potential glyphosate toxicity [10][11][12]. Further, the World Health Organization's International Agency for Research on Cancer concluded that glyphosate is "probably carcinogenic to humans" [13] and Anifandis et al [14,15] demonstrated that glyphosate/PMG induce DNA fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…There is significant interest in the potential impact of environmental toxicity, such as fungicides, insecticides, and herbicides, on male reproductive potential, with several existing publications reporting reductions in semen quality [ 1 , 2 , 3 ]. The reproductive toxicity of bisphenol A (BPA) has aroused concern with our widespread use of plastic products.…”
Section: Introductionmentioning
confidence: 99%